IMPLEMENTASI PEMBUATAN PUPUK ORGANIK BERBAHAN AMPAS JAMU DI MIRACLE FARM CIMANGGIS DEPOK - Usman, Ridwan; Firdaus, Ridwan Awalian; Janudi, Janudi; Wiratmani, Elfitria (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2025)
Agriculture is largely carried out by the Indonesian people, taking into account favourable agricultural conditions and a culture of food security that has relied on agriculture since ancestral times. The national herbal medicine company produces a considerable amount of herbal medicine waste from its production process. Currently, this waste is not being utilised to its full potential and poses environmental problems if not handled seriously, as the company's waste storage space is limited. PT Miracle Farm is a company focused on modern agriculture, utilising available land in Depok City. Its business activities include educational tourism, agriculture, and fisheries, comprising open fields and greenhouses. Farming stages include seedling production, planting, and cultivation processes using fertilisers, with fertiliser procurement requiring significant costs. The solution involves seeking affordable fertiliser options that deliver good quality and results. Training activities on compost production using herbal medicine waste begin with washing the waste, then adding EM4 microbacteria and sugar for compost decomposition, resulting in soil fertility, reduced production costs, and improved environmentally friendly waste management. Sustainable agriculture combines the concepts of the circular economy and waste management. The training aims to boost agricultural productivity at PT Miracle Farm, reduce dependence on chemical fertilisers, and enhance environmental sustainability. The compost production process was successful overall. Pre- and post-tests were conducted to measure the outcomes of the activity, showing significant improvements. This indicates that participants understood the material and gained substantial benefits from the community service, making the training experience valuable.Pertanian sebagian besar dilakukan oleh masyarakat Indonesia dengan mempertimbangkan kondisi pertanian yang mendukung, budaya ketahanan pangan yang mengandalkan pertanian sejak nenek moyang. Perusahaan jamu nasional, sisa produksinya menghasilkan limbah ampas jamu yang cukup berlimpah. Saat ini belum termanfaatkan secara maksimal, dan mengalami permasalahan lingkungan jika tidak ditangani serius, ruang penyimpanan limbah di perusahaan terbatas. PT Miracle Farm adalah sebuah perusahaan yang berfokus pada pertanian modern dengan memanfaatkan lahan yang tersedia di Kota Depok. Kegiatan usahanya melalui wisata edukasi, sektor lain seperti pertanian dan perikanan, terdiri dari lahan terbuka dan rumah kaca Tahapan bertani, pembibitan, menanam, proses penanaman menggunakan pupuk, penyediaan pupuk membutuhkan biaya tidak sedikit. Solusinya mencarikan ide pupuk murah, kualitas dan hasilnya bagus. Kegiatan pelatihan pembuatan pupuk kompos berbahan ampas jamu, pertama pencucian ampas jamu, lalu penambahan mikrobacter EM 4 dan gula untuk pembusukan pupuk kompos, hasilnya untuk kesuburan tanah, menurunkan biaya produksi, dan meningkatkan pengelolaan sampah ramah lingkungan, pertanian berkelanjutan menggabungkan konsep ekonomi sirkular dan pengelolaan sampah. Pelatihan untuk produktivitas pertanian PT Miracle Farm, dan membantu mengurangi ketergantungan pupuk kimia dan meningkatkan kelestarian lingkungan berkelanjutan. Kegiatan pembuatan pupuk kompos secara keseluruhan berhasil. Pretes dan posttest dilakukan untuk pengukuran hasil kegiatan, perolehan peningkatan yang signifikan, indikasi ini menunjukkan peserta paham, mengerti, serta banyak memperoleh manfaat dari pengabdian kepada masyarakat, sehingga pengalaman pelatihan ini dapat bermanfaat.